Activation of Innate Immunity Human Cells by Lipopolisaccharide and Extracellular Polysaccharid Produced by Marine Bacteria - T. P. Smolina; T. S. Zaporozhets; N. N. Besednova (Антибиотики и Химиотерапия, 2020)
It has been shown that using the cytometric method lipopolysaccharide (LPS) and extracellular polysaccharide (EPS) isolated from marine bacteria Pseudoalteromonas nigrifaciens increase the relative amount of monocytes synthesizing IL-12. LPS and EPS enhance the cytotoxic potential of NK cells, enhancing their degranulation (expression of membrane CD107a), intracellular synthesis of IFN-y and increasing the expression of CD25, CD69, HLA-DR, CD11b, and CD54 molecules.